2013
DOI: 10.1099/vir.0.053082-0
|View full text |Cite
|
Sign up to set email alerts
|

Porcine, murine and human sialoadhesin (Sn/Siglec-1/CD169): portals for porcine reproductive and respiratory syndrome virus entry into target cells

Abstract: Porcine sialoadhesin (pSn; a sialic acid-binding lectin) and porcine CD163 (pCD163) are molecules that facilitate infectious entry of porcine reproductive and respiratory syndrome virus (PRRSV) into alveolar macrophages. In this study, it was shown that murine Sn (mSn) and human Sn (hSn), like pSn, can promote PRRSV infection of pCD163-expressing cells. Intact sialic acidbinding domains are crucial, since non-sialic acid-binding mutants of pSn, mSn and hSn did not promote infection. Endodomain-deletion mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As highlighted in a recent review [48], cell surface Siglecs as a group interact with numerous pathogens and pathogen-derived ligands. Interestingly, the macrophage cell surface protein Siglec-1 (Sialoadhesin; CD169), was initially characterized as an important receptor for porcine reproductive and respiratory syndrome virus (PRRSV) [49] although a recent study that monitored PPRSV infection in Siglec-1 gene deleted pigs suggested modification of this hypothesis [50]. Siglec-1 interacts with retroviruses HIV and murine leukemia virus and mediates virion transfer to T lymphocytes [51, 52].…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…As highlighted in a recent review [48], cell surface Siglecs as a group interact with numerous pathogens and pathogen-derived ligands. Interestingly, the macrophage cell surface protein Siglec-1 (Sialoadhesin; CD169), was initially characterized as an important receptor for porcine reproductive and respiratory syndrome virus (PRRSV) [49] although a recent study that monitored PPRSV infection in Siglec-1 gene deleted pigs suggested modification of this hypothesis [50]. Siglec-1 interacts with retroviruses HIV and murine leukemia virus and mediates virion transfer to T lymphocytes [51, 52].…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Earlier studies showed that pCD163 cooperated with another putative receptor, porcine sialoadhesin (Sn/CD169) (23), to facilitate the PRRSV infection, where the former contributed to the uncoating of PRRSV while the latter promoted the attachment and internalization (invasion) of the virus (40)(41)(42)(43)(44)(45)(46)(47)(48). However, one study showed that Sn gene knockout pigs were infected by PRRSV as usual (49), and a recent study using geneedited pigs demonstrates the indispensability of pCD163 (28).…”
Section: Discussionmentioning
confidence: 99%
“…CD169 (Siglec1/Sialoadhesin) is a lectin receptor that mediates uptake of sialylated bacteria and viruses by macrophages (Chang et al, ; Heikema et al, ; Klaas et al, ). These macrophages are known to be permissive for viral replication in mice and pigs due to their ineffective bactericidal mechanisms and higher expression levels of suppressors of cytokine signalling (Honke et al, ; Van Breedam, Verbeeck, Christiaens, Van Gorp, & Nauwynck, ). Using an ex vivo pig spleen perfusion model, they confirmed the role of CD169 + macrophages as a reservoir for intracellular replication of pneumococci within the spleen.…”
Section: Replication Within the Spleenmentioning
confidence: 99%